Jurnalisme Islam di Tengah Transformasi Jurnalistik Digital - Hakim, Lukman (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2019)
This article discusses the concept of Islamic journalism as an alternative to negative journalistic practices as a result of media digitalization which is marked by the birth of the internet, such as the practice of